Head and Neck Cancer Patients' Quality of Life: Analysis of Three Instruments - Elâine Patrícia Alves de Araújo Gomes; Andreza Maria Fabio Aranha; Alvaro Henrique Borges; Luiz Evaristo Ricci Volpato (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: Head and neck cancer treatment has provided better cure and survival rates but the patient's quality of life is still an issue. Purpose: To verify the correlation between the three most used instruments for evaluating the quality of life of head and neck cancer patients. Materials and Method: This cross-sectional study evaluated patients treated for head and neck cancer at the Mato Grosso Cancer Hospital, Cuiabá, MT, Brazil. The variables age, gender, cohabitation status, education, religion, smoking, ethnicity, tumor location and histological type and treatment modality were collected. The patients quality of life was assessed by the Functional Assessment of Cancer Therapy Quality of Life Measurement System (FACT-H&N), University of Washington Quality of Life Questionnaire (UW-QOL), and EORTC QLQ-C30/EORTC QLQ-H&N35 of the European Organization for Research and Treatment of Cancer. Results: The study population consisted of 33 individuals with a mean age of 63.42±11.25 years; 69.70% were males; 54.55% had no partner; 45.45% had only elementary education; 87.9% followed a religion; 84.38% were smokers and 87.50% alcoholics. Squamous cell carcinoma responded for 78.79% of the cases and palate/oropharynx and mouth floor (21.21% each) were the most affected sites. All patients underwent radiotherapy, 90.91% chemotherapy and 63.64% surgery. On the analysis of quality of life, shoulder (UW-QOL), social performance (EORTC QLQ-C30/QLQ-H&N35) and overall well-being (FACT-H&N) had the highest scores while saliva (UW-QOL), nausea and vomiting (EORTC QLQ-C30/QLQ-H&N35) and emotional well-being (FACT-H&N) had the lowest scores. A positive correlation was found between the questionnaires for the patient's overall quality of life and the domains: Pain, Appearan-ce, Activity, Deglutition, Chewing, Speech, Taste, Saliva, Mood and Anxiety. Conclusion: Given the correlation between the questionnaires, the selection of the instrument for future research involving head and neck cancer patients' quality of life should consider the specific aspects to be evaluated.